2019
DOI: 10.3349/ymj.2019.60.10.960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Risk Factors of Anaphylaxis in Pollen-Food Allergy Syndrome

Abstract: PurposeMany studies have reported that pollen-food allergy syndrome (PFAS) can cause anaphylaxis. No comprehensive investigations into anaphylaxis in PFAS have been conducted, however. In this study, we investigated the clinical manifestations and risk factors for anaphylaxis in PFAS in Korean patients with pollinosis.Materials and MethodsData were obtained from a nationwide cross-sectional study that previously reported on PFAS in Korean patients with pollinosis. Data from 273 patients with PFAS were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…[7][8][9] Rarely, patients suffered from lifethreatening anaphylaxis. [10][11][12][13] Regional differences in pollen sensitization patterns influence the prevalence, elicitors, and typical symptoms of PFAS. 14 While much is known about the typical sensitization pattern for PFAS in Northern Europe, 15,16 less information is available for Southern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Rarely, patients suffered from lifethreatening anaphylaxis. [10][11][12][13] Regional differences in pollen sensitization patterns influence the prevalence, elicitors, and typical symptoms of PFAS. 14 While much is known about the typical sensitization pattern for PFAS in Northern Europe, 15,16 less information is available for Southern Europe.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Furthermore, peanut and apple are described as the most common culprit foods causing anaphylaxis in PFAS in Korea, indicating the possible role of Que ac 1, a primary sensitizer, which is homologous to Bet v 1. 24 Molecular characterization of PR‐10 molecules from commonly consumed Korean fruits, such as Korean melon, ginseng, sesame leaf, deodeok, and lotus root, 25 should be done to understand PFAS in more detail. PFAS in Korea should be dependent on the cross‐reaction of Que ac 1 with homologous allergens from commonly consumed fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Lee, et al 24 reported that adult patients with food allergy are allergic to more than two culprit food allergen, and Wang 25 reported that pediatric patients are allergic to three to four culprit food allergens. In addition, because pollen-food allergy syndrome is often associated with pollinosis patients, 26,27 gens might need to be tested during pollen immunotherapy. Therefore, there is a limit in measuring sIgG4 with a singleplex assay.…”
Section: Discussionmentioning
confidence: 99%